How are the classification of students’ mathematical connections in solving non-routine problems? - Kholid, Muhammad Noor; Dewi, Rosita (Al-Jabar: Jurnal Pendidikan Matematika, 2024)
Background: Mathematics is not just a science for its own sake; it is a science that proves to be useful for most other sciences. Mathematical connections play a crucial role in helping students develop a deeper understanding and enhance their thinking about mathematics. These connections represent relationships between different mathematical ideas, between mathematics and other subjects, and between mathematics and everyday life.Aim: This study aims to classify students' mathematical connection abilities when solving non-routine mathematical problems.Method: This research employs a qualitative approach using descriptive and exploratory methods. The study involved 23 students who exhibited mathematical connection skills in problem-solving. Data collection methods included tests, observations, and interviews. The data analysis process consisted of two main stages: data reduction and data presentation. To ensure data validation, the triangulation method was used by comparing the results from the subject tests (answer sheets), observations, and interviews.Results: The findings of this study revealed three distinct classifications of students’ mathematical connections when solving non-routine problems: 1) Patterns; 2) Variables; and 3) ArgumentsConclusion: The implications of these findings suggest that teachers need to be aware of the different classifications of students' mathematical connections. This awareness will enable them to implement mathematics learning strategies that cater to the diverse mathematical connection classifications found in their classrooms. For instance, teachers can utilize different mathematics learning media tailored to students’ learning styles, such as mind, incubation, and visual learning. By doing so, students can better optimize their mathematical connections and achieve improved outcomes in their mathematics learning.